2021
DOI: 10.1017/jfm.2021.887
|View full text |Cite
|
Sign up to set email alerts
|

Absolute instability in shock-containing jets

Abstract: We present an analysis of the linear stability characteristics of shock-containing jets. The flow is linearised around a spatially periodic mean, which acts as a surrogate for a mean flow with a shock-cell structure, leading to a set of partial differential equations with periodic coefficients in space. Disturbances are written using the Floquet ansatz and Fourier modes in the streamwise direction, leading to an eigenvalue problem for the Floquet exponent. The characteristics of the solution are directly compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 72 publications
(148 reference statements)
0
26
1
Order By: Relevance
“…Further, in a consideration of twin jets, which can exhibit a range of different coupling symmetries, it has been demonstrated that only those symmetries where the G-JM is propagative are observed in experimental data . Thus the suggestion of Shen & Tam (2002) that the G-JM might be a component of jet screech appears to have been prescient; however, they suggested that it might be active only in certain mode stages, while the present evidence suggests that the G-JM is actually the upstream component of all screech stages (Nogueira et al 2022b). The G-JM only exists for a finite band of frequencies, and screech tones are observed to fall within this band, and be sharply cut off at its edges.…”
Section: Introductioncontrasting
confidence: 59%
See 4 more Smart Citations
“…Further, in a consideration of twin jets, which can exhibit a range of different coupling symmetries, it has been demonstrated that only those symmetries where the G-JM is propagative are observed in experimental data . Thus the suggestion of Shen & Tam (2002) that the G-JM might be a component of jet screech appears to have been prescient; however, they suggested that it might be active only in certain mode stages, while the present evidence suggests that the G-JM is actually the upstream component of all screech stages (Nogueira et al 2022b). The G-JM only exists for a finite band of frequencies, and screech tones are observed to fall within this band, and be sharply cut off at its edges.…”
Section: Introductioncontrasting
confidence: 59%
“…The result here, however, is underpinned by a fundamentally different concept. Nogueira et al (2022b) demonstrated that screech could be predicted simply through a consideration of mean-flow periodicity, without a requirement that this periodicity arose from shock cells. The present analysis supports the requirement of periodicity (implicit in the use of wavenumber to characterize the flow), but the interpretation of suboptimal peaks in the axial wavenumber spectrum is not necessarily an intuitive one.…”
Section: Interpretation Of the Wavenumber Spectramentioning
confidence: 99%
See 3 more Smart Citations